Synthesis, characterization and photodynamic activity of Sn(iv) triarylcorroles with red-shifted Q bands. (19th November 2019) - Babu, Balaji; Prinsloo, Earl; Mack, John; Nyokong, Tebello
Abstract : A tin(iv )corrole with meso -thien-2-yl rings has significantly red-shifted Q bands and is found to have favourable photodynamic therapy activity. Abstract : Two Sn(iv ) triarylcorroles were synthesised and characterized. The absorption spectrum of a meso -thien-2-yl substituted tin(iv )corrole (1-Sn ) is red shifted compared to its phenyl analogue (2-Sn ) and shows no sign of aggregation in solution. 1-Sn and 2-Sn exhibited singlet oxygen quantum yields of 0.87 and 0.54 in DMF, and have a triplet lifetime of 31 and 50 μs, respectively. Time dependent cellular uptake in MCF-7 cells for 1-Sn reached a peak at 24 h, and 1-Sn was found to be more lipophilic than 2-Sn . 1-Sn showed good photo-cytotoxicity on exposure to a Thorlabs 625 nm LED with an IC50 value of 3.2 μM and remained inactive in the dark.